Analysis of Student Development in Improving Learning Effectiveness Based on The Merdeka Curriculum At Sd Negeri 18 Tungkal Ilir - Amirudin Ria Munanda; Dessy Wardiah; Edi Harapan (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum in improving student development and learning effectiveness at SD Negeri 18 Tungkal Ilir. A descriptive qualitative approach was employed involving the principal, teachers, students, and parents as research participants. Data were collected through participatory observation, semi-structured interviews, documentation, and learning outcome records, and analyzed using the interactive model of Miles and Huberman. The findings reveal that the implementation of the Merdeka Curriculum has enhanced students’ cognitive, affective, and psychomotor development by promoting active, student-centered, and differentiated learning. Students demonstrated higher learning motivation, improved critical thinking, stronger collaboration, and greater learning independence. However, several challenges remain, including limited educational facilities, variations in students’ learning readiness, and teachers’ adaptation to differentiated instruction. Continuous collaboration among teachers, parents, and school management has become an important strategy for overcoming these challenges. This study contributes to educational management by providing empirical evidence on the implementation of the Merdeka Curriculum in supporting holistic student development and improving learning effectiveness in elementary schools.